UAVs’ Dynamic Routing, Subject to Time Windows Variation - Bocewicz, Grzegorz; Radzki, Grzegorz; Nielsen, Peter; Banaszak, Zbigniew (IFAC-PapersOnLine, 2022)
This paper presents a method for the multiple autonomous vehicles mission flight planning in changing weather conditions. We model UAVs fleet servicing spatially-dispersed customers in terms of declarative modelling framework. The considered problem boils down to a predictive and reactive planning of delivery missions within a specified timeframe. Due to the need to implement an emergency return of a UAV to its base, or to handle variations in delivery periods, conditions sufficient to allow eliminating unfeasible solutions, and thus allowing to speed up the calculations, have been developed. The results of numerous computer experiments have confirmed experiments these expectations.